Estimating the quality of life of hemodialysis patients and adequate clearance - Prevyzi, Evangelia; Argyriou, Georgios; Kollia, Thomai; Nestor, Athanasia; Kotanidou, Anastasia; Marvaki, Christina (Health & Research Journal, 2016)
Introduction: Dialysis affects the quality of life of hemodialysis patients due on idrasis in physical activities, psychological factors, and social adaptability. Predominant indicator for assessing the adequacy of dialysis, considered the Kt / V (clearance time/volume of distribution). According to international guidelines, the price which shows adequate dialysis is > 1.2. Aim: The aim of the present study was the association of quality of life of hemodialysis patients with adequate dialysis. Material and Methods: To evaluate the quality of life of hemodialysis patients used the questionnaire KDQOL-SF weighted in the Greek language and the Greek egkyropoiimeno population. Excluded from the study patients with a speaking disability, those who were comatose, aliens, and those undergoing dialysis 3 hours/ 2 times / week. For data processing, used the statistical package SPSS ver.17. Results: Based on the statistical analysis t-test results showed respect to the route of vascular access that patients with graft (31,6%) had a higher clearance rate adequacy, as well as patients undergoing hemodialysis with high permeability (high-flux) filters (35,8%) and those undergoing dialysis with hemodiafiltration (35,8%). According to the statistical criterion pearson's r and multivariate analysis of linear regression, statistically significant difference was only between Kt / V and forefinger encouraging staff and p = 0,032 and p = 0,015 respectively. Conclusions: The conclusions drawn from this study showed that there was no correlation between quality of life and dialysis adequacy, but only with the index of encouraging staff.